Comparison of the efficacy of prophylactic balloon occlusion of the abdominal aorta at or below the level of the renal artery in women with placenta accreta undergoing cesarean section. (3rd August 2021) - Liu, Juanfang; Xu, Jianwei; Jiao, Dechao; Duan, Xuhua; Han, Xinwei
Abstract: Objective: To compare the safety and efficacy of prophylactic balloon occlusion of the abdominal aorta (PBOA) performed at the level of the renal artery (PBOA-ARA) or below this level (PBOA-BRA) for the management of placenta accreta. Methods: We conducted a retrospective investigation of 57 women scheduled for cesarean delivery who underwent PBOA at our hospital between October 2015 and July 2017. The balloon occlusion was performed at (PBOA-ARA group; n = 30) or below (PBOA-BRA group; n = 27) the renal artery origin. The perioperative data of the two groups were compared. Results: Estimated blood loss was lower in the PBOA-ARA group than in the PBOA-BRA group ( p > .05). There were no intergroup differences in intraoperative blood transfusion volume, hemoglobin reduction, urine output, and serum levels of creatinine and blood urea nitrogen. Postballoon release hemorrhage occurred in eight patients of the PBOA-BRA group, but in none of the PBOA-ARA group, indicating a significant difference ( p = .007). Subgroup analysis of placenta types revealed that the estimated blood loss among women with placenta increta in the PBOA-ARA group was less than that in the PBOA-BRA group ( p = .015), which was reflected by a significant difference in the reduction of hemoglobin levels ( p = .042). Conclusions: PBOA at the level of the renal artery entailed lesser blood loss than that performed below the renal artery origin, particularly in the case of placenta increta; this, in turn, reduces the risk of postpartum hemorrhage from ovarian arteries and subsequent blockade of the ovarian artery origin.